A mathematical model for municipal solid waste management – A case study in Hong Kong. (December 2016) - Lee, C.K.M.; Yeung, C.L.; Xiong, Z.R.; Chung, S.H.
Highlights: A municipal solid waste management model is designed based on Asian situations. A model with two linear programming approaches is conducted in Hong Kong. Decision makers can select the model with a proper approach based on preference. A sensitivity analysis indicates the breakeven point for building incinerators. Abstract: With the booming economy and increasing population, the accumulation of waste has become an increasingly arduous issue and has aroused the attention from all sectors of society. Hong Kong which has a relative high daily per capita domestic waste generation rate in Asia has not yet established a comprehensive waste management system. This paper conducts a review of waste management approaches and models. Researchers highlight that mathematical models provide useful information for decision-makers to select appropriate choices and save cost. It is suggested to consider municipal solid waste management in a holistic view and improve the utilization of waste management infrastructures. A mathematical model which adopts integer linear programming and mixed integer programming has been developed for Hong Kong municipal solid waste management. A sensitivity analysis was carried out to simulate different scenarios which provide decision-makers important information for establishing Hong Kong waste management system.